2019
DOI: 10.3389/fnins.2019.01147
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Intermittent Theta-Burst Stimulation as a Treatment for Cocaine Use Disorder: A Proof-of-Concept Study

Abstract: There are no effective treatments for cocaine use disorder (CUD), a chronic, relapsing brain disease characterized by dysregulated circuits related to cue reactivity, reward processing, response inhibition, and executive control. Transcranial magnetic stimulation (TMS) has the potential to modulate circuits and networks implicated in neuropsychiatric disorders, including addiction. Although acute applications of TMS have reduced craving in urine-negative cocaine users, the tolerability and safety of administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 79 publications
(104 reference statements)
1
35
0
Order By: Relevance
“…Preliminary studies in major depression have also reported that twice-daily rTMS appears feasible, tolerable, and capable of achieving efficacy similar to once-daily rTMS while reducing treatment course length twofold (McGirr et al, 2015;Modirrousta et al, 2018;Schulze et al, 2018). A recent study has also shown accelerated iTBS as a treatment for cocaine use disorder (Steele et al, 2019). However, no trials have been published to date that explore the feasibility and clinical effects achieved with accelerated (twice-daily) TBS approaches in methamphetamine-dependent patients.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies in major depression have also reported that twice-daily rTMS appears feasible, tolerable, and capable of achieving efficacy similar to once-daily rTMS while reducing treatment course length twofold (McGirr et al, 2015;Modirrousta et al, 2018;Schulze et al, 2018). A recent study has also shown accelerated iTBS as a treatment for cocaine use disorder (Steele et al, 2019). However, no trials have been published to date that explore the feasibility and clinical effects achieved with accelerated (twice-daily) TBS approaches in methamphetamine-dependent patients.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, researchers are diligently working to understand the mechanisms of change induced by rTMS and the effects related to inherent individual differences in patient populations. Also, there is growing evidence that an engaged circuit is beneficial toward positive outcomes (e.g., VR in Stramba-Badiale et al, 2020) and cocaine cues in Steele et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“… Steele et al (2019). applied accelerated iTBS treatment to the left-dlPFC in cocaine users while they viewed cocaine cues to engage the targeted circuit.Participants reported reduced use (both amount and frequency) 1-month post-treatment.…”
mentioning
confidence: 99%
“…Both rTMS and transcranial direct stimulation (tDCS) have been primarily applied to patients suffering from depression reporting successful enhancement of mood (Wassermann and Zimmermann, 2012;Shin et al, 2015). Transcranial magnetic stimulation has also been employed as a promising alternative to pharmacological therapies, for several other psychiatric disorders which appear to be drug-resistant/non-responsive to medications including bipolar disorder (Xia et al, 2008), schizophrenia (Shi et al, 2014), obsessive-compulsive disorder (Berlim et al, 2013), anxiety disorder (Dilkov et al, 2017), panic disorder (Mantovani et al, 2013), post-traumatic stress disorder (Watts et al, 2012), and addiction disorder (Diana et al, 2017;Hauer et al, 2019;Steele et al, 2019).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) might be effective in modulating circuits and networks implicated in neuropsychiatric disorders and in treating addictions, such as nicotine craving/consumption and cocaine use disorder (Diana et al, 2017;Su et al, 2017;Ma et al, 2019;Steele et al, 2019).…”
Section: Introductionmentioning
confidence: 99%